Teaching/Learning Philosophy In High School: Case Of Congo - Ndossi, Reine Espoire Ngoma; Boundja, Claver (Advances in Social Sciences Research Journal, 2024)
This article is a study and research carried out among students in final year literary classes and Philosophy teachers, at the Nganga Edouard high school in Brazzaville Congo), during the 2019-2020 school year. We wanted to answer the following question: what are the didactic and pedagogical problems that philosophy teachers encounter in the transmission of knowledge related to existence and its problems? This question is linked to the didactics and pedagogy of philosophy in high school. Propose didactics and pedagogy of philosophy, more adapted to the theme entitled “the philosophical teaching of existence and its problems”. We arrive at the following results: the difficulties of philosophical teaching on existence and its problems in literary final year classes are linked to the misuse of didactics and pedagogy by teachers; the theme of existence and its problems is not well taught in high school because of the limitations experienced by teachers regarding the methodical explanation of the subjects; the teaching of this theme is too theoretical and far from the real existence and daily experience of learners. We suggest an interactive didactic approach; a participatory pedagogy; an integration of the real problems of the learners' existence, in the content of the lessons.